Model management and sastainable developmnt of wooden furniture manufactures of de province of Colonel Portillo-Ucayali - Vargas-Espinoza, Jorge L. (2019)
This research aimed to determine the relationship between a model of strategic management and sustainable development of wood furniture manufacturers in the province of Coronel Portillo-Ucayali, also determine the degree of knowledge with manufacturers of furniture Wood on sustainable development; for which a cross-causal correlation was used descriptive analytical methodology. The population is formed by 46 companies dedicated to the transformation of wood raw material whose jurisdiction is the province of Coronel Portillo, department of Ucayali, to which I applied a form of surveys and interviews with owners, customers and suppliers while a parallel survey realize neighboring families. Direct to the processes of supply, production, distribution observation was also used. The results indicate that the correlation is significant. The conclusion of this study is that there is a direct and significant relationship between the model of strategic management and sustainable development of wood furniture manufacturers in the province of Colonel Portillo - Ucayali.